2016
DOI: 10.1093/infdis/jiw425
|View full text |Cite
|
Sign up to set email alerts
|

Humanized Mice Exhibit Increased Susceptibility toStaphylococcus aureusPneumonia

Abstract: Staphylococcus aureus is a highly successful human pathogen that has evolved in response to human immune pressure. The common USA300 methicillin-resistant S. aureus (MRSA) strains express a number of toxins, such as Panton-Valentine leukocidin and LukAB, that have specificity for human receptors. Using nonobese diabetic (NOD)-scid IL2Rγ null (NSG) mice reconstituted with a human hematopoietic system, we were able to discriminate the roles of these toxins in the pathogenesis of pneumonia. We demonstrate that ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 51 publications
(87 reference statements)
4
64
1
Order By: Relevance
“…A recent study using NSG (NOD scid gamma) background mouse strain grafted with human CD34 cells showed increased susceptibility towards clinical isolate USA300 S. aureus strain compared to wild type animals (113). Furthermore, this study identified specific bacterial toxins that were more effective in the humanized mouse strain (113). This indicates that specific host-pathogen interactions drive pneumonia development and illustrates the importance of humanized animal models to study HAP.…”
Section: Humanized Modelsmentioning
confidence: 58%
See 1 more Smart Citation
“…A recent study using NSG (NOD scid gamma) background mouse strain grafted with human CD34 cells showed increased susceptibility towards clinical isolate USA300 S. aureus strain compared to wild type animals (113). Furthermore, this study identified specific bacterial toxins that were more effective in the humanized mouse strain (113). This indicates that specific host-pathogen interactions drive pneumonia development and illustrates the importance of humanized animal models to study HAP.…”
Section: Humanized Modelsmentioning
confidence: 58%
“…A humanized bacterial pneumonia model could offer significant advantages over wild type animals. A recent study using NSG (NOD scid gamma) background mouse strain grafted with human CD34 cells showed increased susceptibility towards clinical isolate USA300 S. aureus strain compared to wild type animals (113). Furthermore, this study identified specific bacterial toxins that were more effective in the humanized mouse strain (113).…”
Section: Humanized Modelsmentioning
confidence: 74%
“…Recent approaches to addressing PVL pathobiology have attempted to circumvent the lack of PVL interaction with murine receptors by using humanized mice models, in which immune incompetent NSG (non-obese diabetic/severe combined immune deficiency/IL2rγ null or NOD.Cg- Prkdc scid Il2rg 1Wjl /SzJ) mice are engrafted with human hematopoietic cells from cord blood (CD34 + ) [145]. These mice are highly susceptible to dermonecrosis and pneumonia caused by PVL-expressing S. aureus in a human PMN-dependent manner [146, 147]. These model systems may provide further insights regarding PVL activity involving the immune response.…”
Section: Cell Surface Receptors For S Aureus Pftsmentioning
confidence: 99%
“…More recently, several reports have addressed modeling S. aureus infections in so-called "humanized" mice (160)(161)(162), which are immunocompromised animals engineered to accept human hematopoietic stem cells and subsequently develop a human immune system (163). Initial reports indicate that humanized mice in the NOD/SCID γ (NSG) background may be an improved model, as a reduced inoculum (up to 1-2 logs lower than that required for WT mice in the soft-tissue model) is able to induce dermonecrosis.…”
Section: Current Challenges In the Translation Of Basic Discoveries Tmentioning
confidence: 99%
“…Initial reports indicate that humanized mice in the NOD/SCID γ (NSG) background may be an improved model, as a reduced inoculum (up to 1-2 logs lower than that required for WT mice in the soft-tissue model) is able to induce dermonecrosis. Moreover, humanized NSG mice exhibit a pathologic phenotype for factors with selective human tropism (160)(161)(162). However, the high cost; the potential confounding by nonimmune compartments, such as epithelial cells; and the incomplete humanization of the immune system, including low neutrophil counts and lack of complement, remain barriers for general acceptance of the model.…”
Section: Current Challenges In the Translation Of Basic Discoveries Tmentioning
confidence: 99%